COASTAL TEACHER TALKS: A PEER-LED PROFESSIONAL LEARNING CIRCLE INITIATIVE - Moh Syahrun Ibrahim; Zulystiawati; Moh. Adriansyah Lahamu (Journal of Community Services on Multidisciplinary Sciences, 2026)
Coastal Teacher Talks is a community service initiative designed to address professional isolation and gender disparities among educators in remote coastal areas of Tomini Bay. Targeting teachers particularly women in geographically marginalized schools, the program aims to strengthen collaborative leadership capacity and improve teaching quality through the establishment of peer-led Professional Learning Circles (PLCs). Using participatory, empowerment-based strategies, the initiative conducts needs assessments, capacity-building workshops, and bi-weekly collaborative teaching circles facilitated by trained teacher leaders. These circles provide structured platforms for dialogue, peer mentoring, reflective practice, and lesson study aligned with Merdeka Belajar principles. The results demonstrate increased teacher collaboration, enhanced confidence and leadership agency among women educators, and the emergence of sustainable, locally driven professional learning cultures. Participating teachers reported reduced professional isolation, stronger shared leadership practices, and improved lesson planning and classroom strategies, indicating that peer-led models can create high-impact, low-resource professional development solutions in coastal contexts.